The teaching and learning of foreign languages in Spain from the sixteenth to eighteenth centuries: influences and inter-relationships*. Issue 1 (1st January 2018) - López, Javier Suso
ABSTRACT: This study of the learning of foreign languages in Spain between the sixteenth and eighteenth centuries sets out to demonstrate the importance of situating research on any given era in a pan-European plurilingual context. A brief historigraphical overview is followed by a discussion of language teaching materials and methods from a sociocultural perspective, highlighting the network of exchanges, adaptations and influences between Spain and the rest of Europe.